Pembuatan Filter Penangkap Emas (Au) Menggunakan Kitin dan Kitosan dari Cangkang Kepiting - Anas, Ajwar; Ahzan, Sukainil; Prasetya, Dwi Sabda Budi (Lensa : Jurnal Kependidikan Fisika, 2017)
[Title: Manufacture of Gold (Au) Capture Filters Using Chitin and Chitosan from Crab Shells]. This study aims to analyze the ratio of absorption capacity between chitin, chitosan and chitin-chitosan mixture from crab shells as a Gold catcher filter (Au). The preparation of chitin and chitosan from crab shells begins with demineralization using 1.5 M HCl, deproteination using 3.5% NaOH and deacetylation using 60% HCl. Chitosan that formed characterized and analyz ed its ability to absorb gold using AAS (Atomic Absorbsion Spectroscopy). The result of analysis using AAS showed that chitin was able to absorb 67.76%, chitin-chitosan mixture 83.57% and chitosan 87.82%. The result showed that chitosan had better absorption percentage to Gold (Au).